2015
DOI: 10.1097/01.naj.0000459638.68657.9b
|View full text |Cite
|
Sign up to set email alerts
|

Fostering Clinical Reasoning in Nursing Students

Abstract: This article is one in a series on the roles of adjunct clinical faculty and preceptors, who teach nursing students to apply knowledge in clinical settings. This article describes why it's important that nursing students develop clinical reasoning skills and how clinical nursing instructors can help them learn these skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…Nurses should deploy different behaviours rather than apply the same behaviour regardless of the situation 35–37. From our perspective as educators, there is a challenge to help students develop response fluency and build relevant skills repertoires37 to care for patients safely.…”
Section: Discussionmentioning
confidence: 99%
“…Nurses should deploy different behaviours rather than apply the same behaviour regardless of the situation 35–37. From our perspective as educators, there is a challenge to help students develop response fluency and build relevant skills repertoires37 to care for patients safely.…”
Section: Discussionmentioning
confidence: 99%
“…During medical education, clinical reasoning is often taught in clinical courses by seeing many patients, actively engaging in problem solving, receiving sufficient feedback and problem-based tutorials with varied and multiple examples of clinical cases (Norman, 2005;Eva, 2005). The learning of clinical reasoning takes time, patience, education, experience and reflection (Koharchik, Caputi, Robb, & Culleiton, 2015). While learning clinical reasoning, students can benefit from an evidence based practical model that demystifies and advance's clinical reasoning skills (Kautz et al, 2005).…”
Section: Teaching Learning and Assessing Clinical Reasoningmentioning
confidence: 99%
“…The literature focusing on nursing practice and analysis of associated errors highlight major challenges related to clinical reasoning processes, especially in newly graduated nurses (Benner et al, 2002; del Bueno, 2005; Eisenhauer, Hurley, & Dolan, 2007; Fero, Witsberger, Wesmiller, Zullo, & Hoffman, 2009; Greenwood, 2000; Koharchik, Caputi, Robb, & Culleiton, 2015; Woods & Doan-Johnson, 2002). Aiken et al (2016) concluded that bedside nurses with higher educational qualifications deliver better patient outcomes.…”
Section: Introductionmentioning
confidence: 99%